2001
DOI: 10.1007/s007050170170
|View full text |Cite
|
Sign up to set email alerts
|

Complete nucleotide sequence of Sesbania mosaic virus: a new virus species of the genus Sobemovirus

Abstract: Summary.The complete nucleotide sequence of the Sesbania mosaic virus (SeMV) genomic RNA was determined by sequencing overlapping cDNA clones. The SeMV genome is 4149 nucleotides in length and encodes four potential overlapping open reading frames (ORFs). Comparison of the nucleotide sequence and the deduced amino acid sequence of the four ORFs of SeMV with that of other sobemoviruses revealed that SeMV was closest to southern bean mosaic virus Arkansas isolate (SBMV-Ark, 73% identity). The 5 non-coding region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…Based on the phylogenetic analysis of 14 RYMV full-length isolates and 58 capsid protein genes sequences, it has been concluded that RYMV evolved in the absence of recombination events (Chare and Holmes, 2006;Fargette et al, 2004). Similarly, on the basis of the phylogenetic comparison of six sobemovirus genomes, including CfMV, RYMV, Lucerne transient streak virus (LTSV), Sesbania mosaic virus (SeMV), Southern cowpea mosaic virus (SCPMV), and Southern bean mosaic virus (SBMV), it was suggested that recombination is neither frequent nor significant in the sobemovirus group (Lokesh et al, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…Based on the phylogenetic analysis of 14 RYMV full-length isolates and 58 capsid protein genes sequences, it has been concluded that RYMV evolved in the absence of recombination events (Chare and Holmes, 2006;Fargette et al, 2004). Similarly, on the basis of the phylogenetic comparison of six sobemovirus genomes, including CfMV, RYMV, Lucerne transient streak virus (LTSV), Sesbania mosaic virus (SeMV), Southern cowpea mosaic virus (SCPMV), and Southern bean mosaic virus (SBMV), it was suggested that recombination is neither frequent nor significant in the sobemovirus group (Lokesh et al, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…NMR studies on cowpea mosaic virus VPg suggested that it does not have any ordered structure (7). In Sobemoviruses, the size of VPg varies between 9 and 12 kDa (8), and it is 9 kDa in SeMV, consisting of 77 amino acid residues (1). The presence of VPg linked to the 5Ј end of the genomic RNA has been confirmed by determining the N-terminal amino acid sequence of VPg in Southern bean mosaic virus, Cocksfoot mottle virus, and SeMV genomic RNA (1, 9, 10).…”
mentioning
confidence: 99%
“…Sesbania mosaic virus (SeMV) 1 belongs to the genus Sobemovirus, which infects Sesbania grandiflora (1). It is an icosahedral virus with T ϭ 3 symmetry, and the capsid is made up of 180 coat protein subunits of molecular mass 29 kDa (2).…”
mentioning
confidence: 99%
See 2 more Smart Citations